How is agroforestry perceived in Europe? An assessment of positive and negative aspects by stakeholders - García de Jalón, Silvestre; Burgess, Paul J.; Graves, Anil; Moreno, Gerardo; McAdam, Jim; Pottier, Eric; Novak, Sandra; Bondesan, Valerio; Mosquera-Losada, María Rosa; Crous-Duran, Josep; Palma, João H. N.; Paulo, Joana A.; et al. (Springer, 2017)
Whilst the benefits of agroforestry are widely recognised in tropical latitudes few studies have assessed how agroforestry is perceived in temperate latitudes. This study evaluates how stakeholders and key actors including farmers, landowners, agricultural advisors, researchers and environmentalists perceive the implementation and expansion of agroforestry in Europe. Meetings were held with 30 stakeholder groups covering different agroforestry systems in 2014 in eleven EU countries (Denmark, France, Germany, Greece, Hungary, Italy, Netherlands, Portugal, Spain, Sweden and the United Kingdom). In total 344 valid responses were received to a questionnaire where stakeholders were asked to rank the positive and negative aspects of implementing agroforestry in their region. Improved biodiversity and wildlife habitats, animal health and welfare, and landscape aesthetics were seen as the main positive aspects of agroforestry. By contrast, increased labour, complexity of work, management costs and administrative burden were seen as the most important negative aspects. Overall, improving the environmental value of agriculture was seen as the main benefit of agroforestry, whilst management and socio-economic issues were seen as the greatest barriers. The great variability in the opportunities and barriers of the systems suggests enhanced adoption of agroforestry across Europe will be most likely to occur with specific initiatives for each type of system.
Keywords: Agroforestry; Adoption; Barrier; Opportunity; Europe